3 Developing competencies and capacity for effective communication and implementation of nutrition research. (18th October 2022) - Wazny, Kerri; Petracchi, Cristina; Laur, Celia; Broadley, Iain; Jaffee, Ally; Buckner, Luke; Lepre, Breanna; Martin, Kathy; Hewett, Lara; Macaninch, Elaine; Bhansali, Abhinav; Jones, Glenys; et al.
Abstract : Policies and guidance alone will likely be insufficient to achieve significant changes in nutrition and health outcomes and a global shift in behaviour is needed. Developing workforce capacity to communicate, implement and scale up effective nutrition interventions is crucial. It is important to ensure that frontline workers, who are in contact with thousands of people every day, have the necessary knowledge, skills and competencies to approach nutrition in an informed, integrated and sensitive way. Despite this need, research in the UK has shown that nutrition training for healthcare professionals is limited and medical students and junior doctors lack confidence and feel underprepared to advise patients on nutrition. Gaps in nutrition capacity development for health professionals might not be a problem only in the UK, with a recent literature review showing that only 44% of medical accreditation and curriculum guidance available internationally integrated nutrition as a content area. Limited nutrition education and training represent a missed opportunity for appropriate action on nutrition. Several initiatives led by organisations in the UK and globally to address this gap were discussed during the 7 th Summit. The FAO elearning Academy, for example, offers free multilingual elearning courses with the aim to prepare professionals to design policies and programmes targeting agriculture, food, nutrition, and health, and transfer the multi- and trans-disciplinary competencies, that are needed. The Nutrition Education Policy in Healthcare Practice (NEPHELP) was another example discussed. NEPHELP delivers workshops that are sensitive to real-world challenges faced by health professionals and promotes the development of nutrition champions that share their learning with others. Culinary Medicine UK also supports medical students and healthcare professionals. It uses a bespoke kitchen as a classroom to teach nutrition through realistic clinical cases and offers opportunities to practice consultation skills. Advocacy in this area has been campaigned by different groups in the UK, including the Nutrition Implementation Coalition, formed by groups such NNEdPro, Culinary Medicine UK, Nutritank and Education and Research in Medical Nutrition Network (ERimNN). An important step in integrating more nutrition content into medical doctors and allied health professionals' education training would be the inclusion of nutrition as a mandatory requirement in accreditation standards, which could act as an incentive for education institutions. Nutrition should be integrated as a cross-cutting theme aligned with core competencies and roles already considered in current standards for health professionals. The UK achieved an important milestone in this domain in 2021 with the launch of the Association for Nutrition Undergraduate Curriculum in Nutrition for Medical doctors. An assessment of the needs and barriers will be conducted with relevant stakeholders to facilitate the implementation of the new curriculum across universities in the UK. In addition to formal education and training in nutrition, another way of supporting nutrition best practices is through curation of relevant research being produced in many parts of the world and their publication free of cost in channels such as BMJ Nutrition, Prevention and Health Journal.